(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: The rapid growth of e-commerce has driven the global expansion of food delivery services. Delivery riders are exposed to multiple occupational hazards due to time pressure, long working hours, and physically demanding tasks. Despite their essential role, research on their health and safety remains fragmented. Methods: This review followed the PRISMA 2020 guidelines. A systematic search was conducted in the MEDLINE and Scopus databases. Only cross-sectional studies involving adult food delivery workers were included. Studies focusing on any type of accident or work-related health problem were considered. Other study designs, such as systematic reviews, were excluded. Studies involving non-food delivery workers or participants under 18 years of age were also excluded. The search was conducted only in English. Keywords and phrases such as “work,” “accidents,” and “delivery rider” were used with Boolean operators. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Prevalence Studies. Results: Occupational hazards were grouped into four categories. Traffic risks included speeding, running red lights, and mobile phone use while driving, with younger and less experienced riders showing a higher risk of accidents. Ergonomic risks were associated with prolonged sitting, vibration exposure, and repetitive movements, contributing to musculoskeletal disorders, particularly in the lower back, neck, and shoulders. Psychosocial risks included stress, burnout, verbal or physical abuse, and job insecurity. Socioeconomic factors, such as dependence on delivery income and lower educational levels, further increased vulnerability and limited access to preventive measures. Conclusion: Food delivery workers face multidimensional risks that affect physical health, mental well-being, and road safety. Addressing these challenges requires comprehensive interventions, including road safety training, ergonomic improvements, psychosocial support, protective equipment, and improved working conditions to reduce accidents and protect worker health.